2012
DOI: 10.1051/0004-6361/201118268
|View full text |Cite
|
Sign up to set email alerts
|

Numerical calculation of convection with reduced speed of sound technique

Abstract: Context. The anelastic approximation is often adopted in numerical calculations with low Mach numbers, such as those including stellar internal convection. This approximation requires so-called frequent global communication, because of an elliptic partial differential equation. Frequent global communication is, however, negative factor for the parallel computing performed with a large number of CPUs. Aims. We test the validity of a method that artificially reduces the speed of sound for the compressible fluid … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 23 publications
5
55
0
Order By: Relevance
“…When a moderate or zero reduction of the speed of sound is used in the near-surface layer while a large ξ around the bottom part of the convection zone is used, the properties of the thermal convection, even including the surface, can be properly investigated without undermining the physics. Hotta et al (2012b) confirmed that the inhomogeneous ξ is valid again when the Mach number is less than 0.7.…”
Section: Reduced Speed Of Sound Techniquesupporting
confidence: 53%
See 3 more Smart Citations
“…When a moderate or zero reduction of the speed of sound is used in the near-surface layer while a large ξ around the bottom part of the convection zone is used, the properties of the thermal convection, even including the surface, can be properly investigated without undermining the physics. Hotta et al (2012b) confirmed that the inhomogeneous ξ is valid again when the Mach number is less than 0.7.…”
Section: Reduced Speed Of Sound Techniquesupporting
confidence: 53%
“…The reduced speed of sound technique (hereafter RSST, Rempel 2005Rempel , 2006Hotta et al 2012b) can overcome these drawbacks while avoiding the severe time step caused by the speed of sound. In the RSST the equation of continuity is replaced with…”
Section: Reduced Speed Of Sound Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…We use the relation ρ = ρ 0 + ρ 1 , p = p 0 + p 1 , and s = s 0 + s 1 . The reduced speed of sound technique (hereafter RSST), which is introduced in Rempel (2005) and Hotta et al (2012b), is used in this study, and ξ denotes the ratio between the original and reduced speed of sound. The investigation of the validity of RSST for the flux rising is given in Hotta et al (in prep.).…”
Section: Modelmentioning
confidence: 99%